Does Aid Promote Electoral Integrity? - Uberti, Luca J.; Jackson, David (The Journal of development studies, 2020)
Since the late 1990s, aid spending for elections has witnessed a dramatic increase. Yet, we lack a comprehensive evaluation of aid effectiveness in this particular programme area. Here, we investigate the impact of aid on electoral integrity using panel data on purpose-disaggregated aid disbursements and a multi-dimensional index of electoral quality from the Varieties of Democracy project. Based on 502 elections in 126 aid-receiving countries during 2002-2015, we estimate a statistically significant effect of election-support ODA on the integrity of elections. The estimated effect is, however, economically small and not very persistent. In the long run, a permanent increase in aid spending by one million US$ leads to an improvement in electoral quality of 1.4 per cent of a standard deviation on the integrity index. We also find that different dimensions of electoral integrity are variably responsive to donor interventions. Additionally, aid spending for elections is subject to diminishing marginal returns, and is less effective at higher levels of development. These findings underline the difficulty of promoting democratic change in countries with adverse structural conditions. Still, donors may improve the cost-effectiveness of electoral assistance programmes by targeting specific countries and prioritising certain types of intervention.